Factors influencing positive subjective health awareness in multicultural adolescents in South Korea: Data from the multicultural adolescents panel study - Sun Yeob Choi (Child Health Nursing Research, 2021)
Purpose This study aimed to identify the factors influencing positive subjective health awareness of middle school-age multicultural adolescents in Korea. Methods This study used data from the fourth to sixth waves of the Multicultural Adolescents Panel Study conducted by the National Youth Policy Institute. In this study, a panel logit model analysis was performed using the Eviews 8.0 program (p<.050). Results Socioeconomic status (r=.02, t=2.13, p=.033), body satisfaction (r=.71, t=1.97, p=.048), and depression (r=-.74, t=2.35, p=.018) influenced positive subjective health awareness in multicultural adolescents. When multicultural characteristics were entered into a statistical model with environmental and personal characteristics, multicultural characteristics did not have a significant influence on positive subjective health awareness. Conclusion Environmental, personal, and multicultural characteristics were related to positive subjective health awareness in multicultural adolescents; thus, an integrated approach considering those variables is recommended. Nursing interventions and educational programs are needed to improve the psychological status of multicultural adolescents and reduce prejudice about them. In addition, nurses need to be sensitive to multicultural characteristics and the developmental characteristics of multicultural adolescents.